Collective intentionality and plural pre‐reflective self‐awareness - Zahavi, D (Wiley, 2018)
In several recent texts, Hans Bernhard Schmid has argued that a proper understanding of collective intentionality and we‐identity requires a convincing account of the “sense of ‘us’” and that headway can be made regarding the latter by drawing on classical theories of self‐awareness (Schmid 2009, 2014a, 2014b). More specifically, Schmid argues that the “sense of ‘us’” amounts to a form of plural pre‐reflective self‐awareness, and as he writes, “Plural pre‐reflective self‐awareness plays the same role in the constitution of a common mind that singular pre‐reflective self‐awareness plays in the individual mind” (Schmid 2014a, 7). At the same time, however, Schmid also acknowledges that “there are important differences to consider,” in “spite of the striking similarities between the plural and the singular mind” (Schmid 2014a, 7). The aim of the following contribution is to assess these claims. How helpful is the appeal to pre‐reflective self‐awareness, and might the differences between the singular and the plural case ultimately overshadow their similarities?